Improving Health Equity for Black Communities in the Face of Coronavirus Disease-2019 - Charlotte Jones-Burton; Kemi Olugemo; Judith R. Greener (Public Health, 2020)
The impact of coronavirus disease-2019 (COVID-19) in the U.S. to date is staggering and Blacks across the country are being infected and dying at rates far in excess of Whites. Although health disparities have been part of America’s reality for decades, the pandemic has exposed the failure of the healthcare system to adequately serve minority patients. There are immediate solu-tions that can help to balance the inequity now and position us well for the future. Five suggested solutions are described which focus on greater inclusion of Blacks in activities such as clinical trials, encouraging community-based resources and providing comprehensive racial data on COVID-19 cases. We are not all in the fight against COVID-19 together. Solutions must be adopt-ed to help to address the current disparities now as well as beyond the immediate crisis.